Examining differentiated instruction dimensions in pre-service teachers’ english lesson plans: a content analysis - Sitti Nurjannah; Muthmainnah Mursidin (Indonesian Institute for Counseling, Education and Theraphy, 2026)
This study examined how differentiated instruction is represented in English lesson plans developed by pre-service teachers in an Indonesian English Language Education program. A qualitative document analysis design was employed using 20 secondary-school EFL lesson plans selected through purposive sampling based on predetermined criteria. The documents were analyzed through deductive qualitative content analysis using six dimensions of differentiated instruction: content, process, product, readiness, interest, and learning profile. Coding was conducted by the researcher using predefined indicators and repeated consistency checks. The findings showed that process differentiation was the most prominently represented dimension, particularly through flexible grouping, collaborative learning, scaffolding, differentiated guidance, and readiness-based support. Content and readiness differentiation were also strongly reflected through contextual materials and diagnostic assessment, whereas product and learning-profile differentiation were less consistently represented. The lesson plans also reflected pedagogical orientations associated with Teaching at the Right Level (TaRL), Problem-Based Learning (PBL), Social Emotional Learning (SEL), and Culturally Responsive Teaching (CRT). These findings indicate that pre-service teachers were more prepared to differentiate instructional processes and readiness-based support than to design varied learning products and individualized learning-profile adaptations. The study contributes to EFL teacher education by identifying strengths and gaps in differentiated instructional planning and highlighting areas requiring further pedagogical support.